2009
DOI: 10.1111/j.1464-410x.2009.08505.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function among women with stress incontinence after using transobturator vaginal tape, and its correlation with patient’s expectations

Abstract: function, the Beck depression indices and their expectation of sexual function after surgery. RESULTSSixty-two premenopausal sexually active women were included (mean age 40.5 years). The cure rate from SUI was 92%, 89%, 87% and 84% at 6, 12, 18 and 24 months, respectively. All patients attended the visit before and the first visit after surgery, while 71%, 42% and 24% were assessed at the 12-, 18 and 24-month visits, respectively. The mean follow-up was 12 months. Fiftytwo women resumed their sexual activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…[31], Pace and Vicentini [28], and El Enen et al. [23] appear to show more significant improvement in sexual function compared with other studies. However, all three studies are well conducted, use a validated questionnaire for assessment of sexual function, and have appropriate follow‐up of greater than 3 months.…”
Section: Discussionmentioning
confidence: 67%
“…[31], Pace and Vicentini [28], and El Enen et al. [23] appear to show more significant improvement in sexual function compared with other studies. However, all three studies are well conducted, use a validated questionnaire for assessment of sexual function, and have appropriate follow‐up of greater than 3 months.…”
Section: Discussionmentioning
confidence: 67%
“…The rate of women having 5-8 coital activities/month increased from 23% in the preoperative period to 33% in the postoperative 6 months, but the difference was not statistically significant. El-Enen et al [34] evaluated sexual functions in 62 women who underwent TOT operation. In the postoperative 6 months 57% had the same frequency of sexual activity, 31% had an increase in sexual activity, and 13% had a decrease in sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly; in a prospective study done in 2009 where 62 TOT surgery patients participated, it was noted that there were increases in 18 Zhang Z, (2016), 28 Zyczynski HM, (2012), 11 TOT FSFI total scores, sexual desire, arousal, satisfaction, and lubrication. Besides, this study indicated that after 8 weeks following the surgery, women became able to have a sexual relationship once a week (15).…”
Section: Comparing Fsfi Resultsmentioning
confidence: 69%